108k views
4 votes
Please solve!!!!thanks

Please solve!!!!thanks-example-1
User Uelordi
by
5.6k points

2 Answers

0 votes

Answer:

h = 11. 5.

Step-by-step explanation:

(4h - (21 - 8h)/3 = (15 + 6(h - 1)/2

Cross multiplying, we get:

2(4h - (21 - 8h) = 3(15 + 6(h - 1)

8h - 2(21 - 8h) = 45 + 18(h - 1)

8h - 42 + 16h = 45 + 18h - 18

8h + 16h - 18h = 45 - 18 + 42

6h = 69

h = 11. 5

User Athan
by
3.9k points
4 votes

Answer:

h = 11. 5.

Explanation:

(4h - (21 - 8h)/3 = (15 + 6(h - 1)/2

Cross multiplying, we get:

2(4h - (21 - 8h) = 3(15 + 6(h - 1)

8h - 2(21 - 8h) = 45 + 18(h - 1)

8h - 42 + 16h = 45 + 18h - 18

8h + 16h - 18h = 45 - 18 + 42

6h = 69

h = 11. 5

User Harold
by
5.6k points